The fracture behaviors of monolayer phosphorene with grain boundaries under tension: a molecular dynamics study. Issue 30 (13th July 2016) - Guo, Yangyang; Qiao, Chong; Wang, Aihua; Zhang, Jinping; Wang, Songyou; Su, Wan-Sheng; Jia, Yu
Abstract : The fracture behaviors of monolayer phosphorene with and without a grain boundary have been explored by molecular dynamics simulations. Abstract : The fracture behaviors of monolayer phosphorene (MP) with and without a grain boundary (GB) have been explored by molecular dynamics (MD) simulations. Firstly, in the case of perfect MP, fracture mostly happens on the bond in the zigzag direction when suffering random loading. With the existence of a GB, the crack propagates perpendicular to the GB in different ways under parallel tension to the GB, whereas it propagates along the GB under perpendicular tension to the GB. Then, we found that both the fracture strength and strain decrease with increasing temperature making fracture more likely at relatively high temperatures. Finally, we also found that, similar to graphene, the effect of strain rate on both the fracture strength and strain is not significant, demonstrating that MP is a typical brittle 2D material. Overall, our findings present a useful insight into utilizing phosphorene for mechanical design in electronic devices.